A Comparison of the Scotland Yard Test Amidoprine/H202 and “Okokit”* in the Routine Detection of Faecal Occult Blood (Res Medica, 2014)
Concern about the possible carcinogenic properties of o-tolidine and benzidine has led to a search for less harmful reagents for use in the detection of occult blood in faeces. The new preparations — Amidopyrine and Okokit — were compared with the standard method of the Scotland Yard Test. Amidopyrine and Okokit are believed to be non-carcinogenic reagents.  The active ingredient of the Ham’s reagent used in the Scotland Yard Test is aminophthalhydroxide and is likewise not implicated in carcinogenesis.The chief aim of this study was purely practical in elucidating, for purposes of sideroom testing, the efficacy of the three tests.  In the Scotland Yard Test, Ham’s reagent (5 drops) is added to each labelled carton containing a faecal sample to be tested. This is followed by the addition of 5 drops of H2O2.  The fluorescent blue / purple colour, indicating a positive result, appears immediately, and the shadow cast by the container wall is sufficient for the colour to be seen readily in daylight.  No sample preparation is required and sequential testing of many specimens is possible using this technique.